Developmental Safety Profile of the Anti-HIV Agent Stampidine in Rabbits - D'Cruz, Osmond J.; Erbeck, Douglas; Uckun, Fatih M. (Arzneimittelforschung, 2006)
Stampidine (STAMP, DDE-113, HI-113, N-[p-(4-bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine methyl ester, CAS 217178-62-6) is a novel aryl phosphate derivative of stavudine (STV, d4T, 2',3'-didehydro-3'-deoxythymidine, CAS 3056-17-5) with potent anti-HIV activity. The reproductive and developmental safety profile of STAMP was evaluated in mated New Zealand white rabbits. STAMP did not adversely affect the reproductive health of female rabbits and it lacked teratogenicity or other developmental toxicity in their progeny.
Keywords: Anti-HIV agents, chemoprophylaxis; Antiretroviral therapy; N-[p-(4-Bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine methyl ester; CAS 217178-62-6; DDE-113; HI-113; Stampidine, chemoprophylaxis, reproductive safety